Older Malaysian taxi drivers: working environment in the new norm from ergonomic perspective - Mohd Yusoff, Irwan Syah; Sabri, Mohamad Fazli; Mohd Tamrin, Shamsul Bahri; Abu Ujum, Diana (Human Resource Management Academic Research Society, 2021)
Driving taxi is the alternative occupations taken up by older individuals during the COVID-19 pandemic, which can support household incomes in such challenging times. This paper aims to study the working environment among older taxi drivers in Malaysia through an ergonomic approach. A cross-sectional study was led utilizing a self-administered survey. Purposive method sampling was used based on inclusive criteria. A total of 443 respondents joined the survey. The Chi-square method was utilized to analyse the data using SPSS software version 2.0. More than half of respondents (70.0%) felt MSDs symptom injuries on their lower backs for the past 12 months and 75.4% in the last seven days. There is a significant relationship (p< 0.05) between variables; BMI, smoking status, carrying luggage into the trunk, feeling back pain were mainly due to the seat design and long-distance driving. Inappropriate working attitudes may cause discomfort towards developing MSDs and injuries at upper body parts. The implication of awareness programs and ergonomic approaches for work purpose might positively affect the family’s well-being and the safety, and health of older Malaysian taxi drivers when adopting a new norm working environment during the Covid-19 crisis.